2004
DOI: 10.1002/ejsp.218
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating interests or values and reaching integrative agreements: the importance of time pressure and temporary impasses

Abstract: Negotiation research and theory tends to focus on interests and ignores values. This experiment compared the influence of negotiations about interests with negotiations about values under low or high time pressure. Results showed that (1) individuals got locked into early impasses more often under low than high time pressure, (2) getting locked into early impasse produced a switch from low levels of integrative behaviour early in the negotiation to high levels late in the negotiation, but only when interests r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 36 publications
7
75
0
2
Order By: Relevance
“…For example, case analyses of labor-management negotiations (Walton & McKersie, 1965) as well as laboratory experiments (Harinck & De Dreu, 2004;Olekalns & Smith, 2005) These research findings and case observations resonate well with the idea that temporary breaks in negotiation allow participants to cool off, to reflect upon the interaction process and to evaluate behavior and strategies. Indeed, Ury (1991) advises negotiators to frequently take a break, and to 'go to the balcony'; to detach oneself physically and mentally from the negotiation to evaluate it as if one were a third party.…”
Section: Take a Break! Or Not? The Impact Of Mindsets During Breaks Omentioning
confidence: 63%
See 2 more Smart Citations
“…For example, case analyses of labor-management negotiations (Walton & McKersie, 1965) as well as laboratory experiments (Harinck & De Dreu, 2004;Olekalns & Smith, 2005) These research findings and case observations resonate well with the idea that temporary breaks in negotiation allow participants to cool off, to reflect upon the interaction process and to evaluate behavior and strategies. Indeed, Ury (1991) advises negotiators to frequently take a break, and to 'go to the balcony'; to detach oneself physically and mentally from the negotiation to evaluate it as if one were a third party.…”
Section: Take a Break! Or Not? The Impact Of Mindsets During Breaks Omentioning
confidence: 63%
“…The authors found that negotiation outcomes improved when the negotiation was characterized by more facilitating than inhibitory turning points. Similarly, Harinck and De Dreu (2004) showed that naturally occurring temporary recesses early in a negotiation related to more integrative behavior late in the negotiation.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The negotiation process often follows a differentiation-before-integration pattern [16], where the negotiation starts with distributed behaviours until an impasse is reached, and then the participants switch to integrative behaviours to avoid failure.…”
Section: Sqfd and Negotiation -Requirements Definitionmentioning
confidence: 99%
“…According to [16], the switch to the integrative behaviour requires the combination of two conditions: an impasse and the willingness to engage in integrative behaviours. We investigate another alternative: using groupware to foster users engaging in integrative behaviours.…”
Section: Sqfd and Negotiation -Requirements Definitionmentioning
confidence: 99%